PEMBERDAYAAN PENYANDANG DISABILITAS PADA PROGRAM PERMATABRAVE CORPORATE SOCIAL RESPONSIBILITY (CSR) BANK PERMATA TBK - Wahyudi, Ayuananda (Program Studi Ilmu Kesejahteraan Sosial FISIP UNPAS, 2023)
The right to access to work is one of the problems for persons with disabilities, many of them cannot find work due to their low educational background and lack of skills. Through empowerment such as the Corporate Social Responsibility (CSR) program that exists in every company, it can help persons with disabilities in meeting their daily needs by becoming worker or employee in a company. One company that has a CSR program for people with disabilities is Permata Bank. So based on this background, researchers are encouraged to conduct in-depth research on Corporate Social Responsibility (CSR), so that this thesis will be entitled: